Women's Awqaf in the Arab Islamic state on mosques and Masjids - Badie M. Ibrahim; Marwa M. Ghazi (مجلة جامعة الأنبار للعلوم الإنسانية, 2022)
The study targeted the contribution of women to the endowment of mosques and mosques throughout the historical ages, because of their belief in its religious, scientific, educational and charitable impact. the side . The endowment for mosques is one of the most important financial resources in order to continue to perform the duties and tasks that it performs, such as the role of memorizing the Holy Qur’an, supporting preachers and preachers in practicing their roles in developing the meanings of goodness and truth, urging jihad for the sake of God, and addressing people’s issues and problems in life